HUBUNGAN TINGKAT PENGETAHUAN DAN PEMBERANTASAN SARANG NYAMUK DENGAN TERJADINYA DEMAM BERDARAH DENGUE (DBD) DI PUSKESMAS LUMPATAN - Rahim, Supli Effendi; Arapat, Yasser; Sholiha, Lia (Journal Safety and Healthty, 2024)
Dengue Hemorrhagic Fever or abbreviated as DHF is a disease caused by the dengue virus which is transmitted through the bite of the Aedes aegypti and Aedes albopictus mosquitoes. This study aims to determine the relationship between knowledge and eradication of mosquito nests with the incidence of DHF. This type of research uses cross sectional. The population in this study was 60 people with a sampling technique with a total sampling of 60 respondents. The analysis was carried out in two stages, namely Univariate and Bivariate analysis. The statistical test used the chi-square test with a significance level of =5%. The results showed that there was a significant relationship between the level of knowledge and eradication of mosquito nests simultaneously with the occurrence of dengue hemorrhagic fever at the Lumpatan Health Center. The results of this study can be used as a reflection to improve and improve the performance of existing programs related to dengue disease in the working area of ​​the Puskesmas. So that later it can increase public knowledge about dengue prevention through these programs.